The copper transporter, Ctr4, and the microtubule-associated protein, Cgp1, are important for Cryptococcus neoformans adaptation to nitrogen availability. Issue 19 (19th October 2021) - Bosch, Caylin; Volschenk, Heinrich; Botha, Alfred
ABSTRACT: Nitrogen limitation was previously shown to be an important regulator of several genes associated with virulence in Cryptococcus neoformans . Among the most highly expressed genes under low-nitrogen conditions were CTR4 and CGP1, encoding a copper transporter and a microtubule-associated protein, respectively. However, the functional association of these genes with nitrogen limitation—a nutritional stress experienced in both environment and host—remains to be determined. Moreover, whether increased CTR4 and CGP1 expression is linked to the enhanced cryptococcal drug tolerance previously observed in low-nitrogen conditions is yet to be elucidated. Therefore, the present study explored the role of Cgp1 and Ctr4 in C. neoformans nitrogen stress adaptation and antifungal susceptibility. Our results showed that these genes play a role in the growth of C. neoformans in nitrogen-limited media, nitrogen source assimilation and growth on nitrogen-poor woody debris. Furthermore, we demonstrate that both Ctr4 and Cgp1 contribute to oxidative stress and antifungal susceptibility, with a ctr4∆ mutant being more susceptible to fluconazole and a cgp1∆ mutant being more susceptible to fluconazole and amphotericin B. Overall, our findings improve our understanding of the role of Ctr4 and Cgp1 in cryptococcal drug tolerance and adaptation to nitrogen availability. Abstract : The virulence-associated genes, CTR4 and CGP1, are functionally associated with low-nitrogen conditions, contributing to Cryptococcus neoformans growth in nitrogen-limited media, nitrogen source utilization and antifungal susceptibility.